Influence of Social Networks and Social Media toward Satisfaction through Apparel Purchase Decision on Adolescents in East Java - Christina Esti Susanti (International Journal of Supply Chain Management, 2017)
This study aims to determine the influence of Social Media and Social networks toward satisfaction through consumer purchasing decisions apparel at teenagers in East Java. The population used in this study are young people in East Java. According to the Central Statistics Agency (2010), adolescent age limit is 10 to 24 years of age. Characteristics of the sample in this study are: a minimum age of 17 years, have social networks, social media has, and never make a purchase apparel for information from social networks. Total sample of 150 respondents. Sampling techniques or sampling technique in this study were randomized (random sampling), the sampling technique that gives equal opportunity for each element or member of the population to be selected into the sample. The technique used to draw the sample is purposive random sampling technique. The analysis technique used to perform data processing in this peneitian is a structural equation model (SEM). The research proves that the hypothesis proposed in this study are: (1) social networks positive and significant effect on purchasing decisions apparel to consumers adolescents in East Java, (2) social media positive and significant effect on purchasing decisions apparel to consumers teenagers in East Java, (3) the purchase decision apparel positive and significant impact on satisfaction on consumer teenagers in East Java, (4) social networks positive and significant effect on satisfaction through the purchasing decisions of apparel to consumers adolescents in East Java, (5) social media positive and significant effect on satisfaction through the purchasing decisions of consumers apparel at teenagers in East Java, and (6) social networks and social media, and a significant positive effect on satisfaction through consumer purchasing decisions apparel at teenagers in East Java; be accepted. Suggestions for future research is to expand the variable which in theory are stated to have influence on purchasing decisions and satisfaction.